2011
DOI: 10.1002/cssc.201000341
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water as Reaction Environment: Fundamentals of Hydrothermal Biomass Transformation

Abstract: Subcritical water, that is, water above the boiling and below critical point, is a unique and sustainable reaction medium. Based on its solvent properties, in combination with the often considerable intrinsic water content of natural biomass, it is often considered as a potential solvent for biomass processing. Current knowledge on biomass transformation in subcritical water is, however, still rather scattered without providing a consistent picture. Concentrating on fundamental physical and chemical aspects, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(199 citation statements)
references
References 156 publications
(224 reference statements)
6
193
0
Order By: Relevance
“…These results were in accordance with the work of Zakaria et al (2015a), who reported a similar decrease in the pH from 4.10 to 3.39 when the temperature increased from 170 to 210 °C during the hydrothermal pretreatment of oil palm frond fibre (OPFF). The decrease in pH was attributed to the accumulation of acetic acid, which resulted from the cleavage of acetyl groups located in the hemicellulose matrix, and resulted in hemicellulose degradation (Möller et al 2011;Xiao et al 2013;Ho et al 2014).…”
Section: Effect Of Hpsp On Weight Loss Ph and Chemical Composition mentioning
confidence: 99%
“…These results were in accordance with the work of Zakaria et al (2015a), who reported a similar decrease in the pH from 4.10 to 3.39 when the temperature increased from 170 to 210 °C during the hydrothermal pretreatment of oil palm frond fibre (OPFF). The decrease in pH was attributed to the accumulation of acetic acid, which resulted from the cleavage of acetyl groups located in the hemicellulose matrix, and resulted in hemicellulose degradation (Möller et al 2011;Xiao et al 2013;Ho et al 2014).…”
Section: Effect Of Hpsp On Weight Loss Ph and Chemical Composition mentioning
confidence: 99%
“…Hydrothermal depolymerization is also an efficient process for biomass utilization (Demirbas 2010;Moeller et al 2011;. For example, Akhtar et al (2010) reported that empty palm fruit bunches could be liquefied efficiently in alkaline hot compressed water, where more than 60.1% of liquid products were phenolic; however, aromatic bio-char was generated.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the selectivity of the unidentified products decreased markedly before 1.5 h, and then increased remarkably with prolonged time. After 1.5 h, the decomposition of the C-C bond cleavage products to gas products or humins could easily take place (Möller et al 2011;Yin and Tan 2012). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%